Survei kepuasan terhadap penggunaan aplikasi “Sepekan” - Indarto, Tomi; Kholifah, Anik Nur; Widiyawati, Wiwik; Mulyani, Endah; Musfara, Deah Dwi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The use of information technology and digitalization to develop public services is known as e-government. One example is the